2003
DOI: 10.4049/jimmunol.171.9.4786
|View full text |Cite
|
Sign up to set email alerts
|

Complement Regulatory Protein C1 Inhibitor Binds to Selectins and Interferes with Endothelial-Leukocyte Adhesion

Abstract: C1 inhibitor (C1INH), a member of the serine proteinase inhibitor (serpin) family, is an inhibitor of proteases in the complement system, the contact system of kinin generation, and the intrinsic coagulation pathway. It is the most heavily glycosylated plasma protein, containing 13 definitively identified glycosylation sites as well as an additional 7 potential glycosylation sites. C1INH consists of two distinct domains: a serpin domain and an amino-terminal domain. The serpin domain retains all the protease-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
82
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 85 publications
(89 citation statements)
references
References 46 publications
4
82
2
1
Order By: Relevance
“…Combined with our previous observations in LPS-induced endotoxin shock and in TNF-␣-induced leukocyte rolling (39,44,61,62), and other published studies (26,27), the studies described in this work demonstrate that C1INH exerts its antibacterial and anti-inflammatory functions via several different mechanisms. These include, in addition to complement and contact system inhibition, the direct interaction of C1INH with endotoxin LPS (and with LPS-containing bacteria) and the inhibition of selectin-mediated leukocyte rolling (61,62).…”
Section: Discussionmentioning
confidence: 68%
“…Combined with our previous observations in LPS-induced endotoxin shock and in TNF-␣-induced leukocyte rolling (39,44,61,62), and other published studies (26,27), the studies described in this work demonstrate that C1INH exerts its antibacterial and anti-inflammatory functions via several different mechanisms. These include, in addition to complement and contact system inhibition, the direct interaction of C1INH with endotoxin LPS (and with LPS-containing bacteria) and the inhibition of selectin-mediated leukocyte rolling (61,62).…”
Section: Discussionmentioning
confidence: 68%
“…We have demonstrated that C1INH plays a direct role in modulating leukocyte adhesion in acute inflammation and intestinal ischemia and reperfusion models (4,5,26). C1INH binds to selectins, interferes with leukocyte-endothelial adhesion, and suppresses leukocyte transmigration across the endothelium (4,5). This activity is not related to its protease-inhibitory function because the reactive center-cleaved inactive form is as potent as the native form.…”
Section: Discussionmentioning
confidence: 94%
“…The treatment with C1INH in WT mice reversed the elevated tissue MPO levels in response to DSS, consequently limiting the tissue damage, and suppressed the development of the DSS-induced colitis. We have demonstrated that C1INH plays a direct role in modulating leukocyte adhesion in acute inflammation and intestinal ischemia and reperfusion models (4,5,26). C1INH binds to selectins, interferes with leukocyte-endothelial adhesion, and suppresses leukocyte transmigration across the endothelium (4,5).…”
Section: Discussionmentioning
confidence: 99%
“…C1-INH can inhibit classical pathway complement activation by binding to C1r and C1s. It also binds to P-and E-selectins and interferes with leukocyte adhesion [41]. Since its anti proteolytic activity appears to be preserved after binding to P-selectin, C1-INH expression on PMP may limit the generation of C3a and C5a [42,43].…”
Section: Discussionmentioning
confidence: 99%